KESADARAN HUKUM MASYARAKAT DALAM PEMBUATAN SURAT IZIN MENGEMUDI (SIM) C DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Siti Nurlailiyah; Hambali Hambali; Jumili Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is based on explaining the level of legal awareness of the community of Tebing Tinggi District, Kepulauan Meranti Regency in making a driver’s license (SIM) C. Basically, there is awareness of the law in every human being. To create a law-conscious society, it is necessary to know, understand, obey and respect the law. Driver’s licence (SIM) as an instrument of protection of interests and legal certainty for every community who drives a vehicle in obedience to traffic. The formulation of the problem to be examined in the research is How the Level of Public Legal Awareness in the Making of a Driving License (SIM) C in Tebing Tinggi District, Kepulauan Meranti Regency. The purpose of this study was to determine the level of community legal awareness of Tebing Tinggi District, Kepulauan Meranti Regency in the making a driver’s license (SIM) C. This study used a quantitative descriptive method. The data collection instrument used in this study was a questionnaire consisting of 4 indicators with 20 questions. The population in this study were the people of Tebing Tinggi District. The sample in this study was taken using the incidental sampling technique. Based on the results of research and discussion of respondents who answered "Less Knowing", namely 34.1%, it is in the range of 25.01% - 50.00% including in the category of "Less Aware" answers. This illustrates that the community in Tebing Tinggi district, Kepulauan Meranti Regency is less aware of the compliance in making a driver’s licence (SIM) C.Key Words: Public Legal Awareness, Driver’s Licence (SIM) C